2009
DOI: 10.1177/1087054708329927
|View full text |Cite
|
Sign up to set email alerts
|

Ability of College Students to Simulate ADHD on Objective Measures of Attention

Abstract: The implications of these findings highlight the importance of relying on multiple vectors of information, be it objective, observational, self-report, or reports by others, when diagnosing ADHD and assessing factors related to potential secondary gain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
81
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(86 citation statements)
references
References 57 publications
4
81
1
Order By: Relevance
“…Sollman et al [17] evaluated the usefulness of ADHD symptom checklists, neurocognitive tests, and symptom validity tests (i.e., measures, such as the Word Memory Test, initially developed to detect feigned neurocognitive or psychiatric dysfunction), in discriminating between students instructed to feign ADHD and those known to have the disorder. As found in other studies [18], ADHD self-report scales did not accurately differentiate these groups [17]. Widely used neuropsychological assessments and objective measures of attention (i.e., the Conners' Continuous Performance Test [19]), also were not effective [17].…”
Section: Malingeringmentioning
confidence: 56%
“…Sollman et al [17] evaluated the usefulness of ADHD symptom checklists, neurocognitive tests, and symptom validity tests (i.e., measures, such as the Word Memory Test, initially developed to detect feigned neurocognitive or psychiatric dysfunction), in discriminating between students instructed to feign ADHD and those known to have the disorder. As found in other studies [18], ADHD self-report scales did not accurately differentiate these groups [17]. Widely used neuropsychological assessments and objective measures of attention (i.e., the Conners' Continuous Performance Test [19]), also were not effective [17].…”
Section: Malingeringmentioning
confidence: 56%
“…Research on malingered ADHD has most often employed a simulation study design, in which a group of participants is instructed and incentivized to feign symptoms of ADHD while completing a battery of psychological tests (Booksh 2005;Fisher 2007;Harrison et al 2007;Jachimowitz and Geiselman 2004;Leark et al 2002;Quinn 2003;Sollman et al 2010). Although it is impossible to experimentally manipulate true malingering in a clinical setting, the simulation design allows examination of how persons might feign a disorder when faced with incentives to feign believably.…”
mentioning
confidence: 99%
“…The more rigorous studies of malingered ADHD have tended to focus on validating symptom validity tests designed to detect cognitive malingering, the intentional production of impaired performance on measures of cognitive abilities, such as memory and attention (Booksh 2005;Leark et al 2002;Sollman et al 2010). Research on malingering of psychiatric symptoms of ADHD has established that persons instructed to simulate ADHD symptoms tend to produce symptom profiles similar in severity to honest clinical controls and more severe than honest nonclinical controls (Booksh 2005;Harrison et al 2007;Jachimowitz and Geiselman 2004;Quinn 2003;Sollman et al 2010).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…No using of clinical assessment to evaluate the results of the ASRS Screener was one of the limitations of current study that may have caused to a higher prevalence rate of ADHD symptoms. In addition high prevalence rates of ADHD symptoms may be a result of limitation of DSM-IV criteria (Barkley, Murphy, & Fischer, 2010) and the scales developed based on its criteria, or feigning and exaggerating ADHD symptoms by college students (Jasinski et al, 2011;Lee Booksh, Pella, Singh, & Drew Gouvier, 2010;Sollman, Ranseen, & Berry, 2010). Kessler et al (2006) found that Adult ADHD is co-morbid with other mental disorders such as mood disorder, Anxiety disorder, substance use disorder and impulsive control disorder.…”
Section: Discussionmentioning
confidence: 99%